2014
DOI: 10.1136/bmjopen-2014-005125
|View full text |Cite
|
Sign up to set email alerts
|

A population-based cross-sectional study of barriers to uptake of eye care services in South India: the Rapid Assessment of Visual Impairment (RAVI) project

Abstract: ObjectiveTo assess the barriers to uptake of eye care services among those with avoidable impairment in the population aged ≥40 years in the South Indian state of Andhra Pradesh.DesignCross-sectional study.SettingCommunity setting.ParticipantsOf 7800 participants recruited from one urban and two rural locations using a two-stage cluster random sampling methodology, 7378 (95%) were examined. Eye examinations were conducted using a rapid assessment protocol. Visual impairment (VI) was defined as presenting visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 20 publications
6
61
0
Order By: Relevance
“…There is some evidence for this from other studies where usage of eye care services is reported. The studies on barriers have shown a decline in the proportion of people who reported accessibility as a barrier for the uptake of eye care services in Andhra Pradesh 16. Studies have also reported a higher prevalence of spectacles among rural women compared with men, suggestive of higher uptake of services 17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence for this from other studies where usage of eye care services is reported. The studies on barriers have shown a decline in the proportion of people who reported accessibility as a barrier for the uptake of eye care services in Andhra Pradesh 16. Studies have also reported a higher prevalence of spectacles among rural women compared with men, suggestive of higher uptake of services 17…”
Section: Discussionmentioning
confidence: 99%
“…We found that those who were educated had lower odds of having VI. It is possible that those who were educated had better awareness, affordability and access to eye care services compared with their uneducated counterparts 16. This can also partly be attributed to higher visual demands among those who were educated.…”
Section: Discussionmentioning
confidence: 99%
“…Dhaliwal and Gupta and Patel et al [16,17] reported person-related (attitude) barriers to be major barriers to utilization of eye care services in Indians. A study in southern India by Marmamula et al [18] reported the lack of perceived need for eye care services to be the leading person-related barrier to utilization of eye care services. Other studies have reported similar findings [10,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…11 The cost of childhood cataract is far greater than for adult surgery, as specialized surgical centers may lie at a great distance; family members need to travel with the child; inpatient stays are longer; hospital charges are higher due to more prolonged surgery and the need for general anesthesia; regular follow up is essential for optimal visual outcomes; and children may need to change spectacles frequently as the eyes develop. 12,13 Although there are studies showing cost as one of the barriers to uptake of cataract surgery in China and India 14,15 , few have investigated the economic impact of cataract surgery on children and families. We carried out a pilot questionnaire survey in Shanxi Eye Hospital, China and Vivekananda Mission Asram Netra Niramay Niketan, India, to explore the barriers and costs associated with the detection and management of pediatric cataract in India and China.…”
Section: Introductionmentioning
confidence: 99%